Medial Patellofemoral Ligament Reconstruction: The Superficial Quad Technique. (May 2013) - Goyal, Deepak
Background: Medial patellofemoral ligament (MPFL) reconstruction is a routine procedure for patellar instability. The majority of the techniques require hardware fixation or a bony procedure at the patella. However, most of the complications described in the literature can be attributed to patellar fixation. The "superficial quad technique" uses the superficial slip of the quadriceps tendon as the graft material, which provides a better anatomic match to the native MPFL. Hypothesis: The superficial quad technique provides anatomic patellar fixation without a bony procedure and without patellar complications. Study Design: Case series; Level of evidence, 4. Methods: The study included 32 patients (10 male, 22 female; mean age, 25 years) who underwent MPFL reconstruction using the superficial quad technique and who were followed for a mean duration of 38 months. Objective assessment was performed and Kujala scores were obtained preoperatively and at the time of final follow-up. Results: There were no patellar complications, including redislocation, in the present study. The mean Kujala score improved to 91.25 (range, 73-100) from a preoperative score of 49.31 (range, 23-62). Conclusion: The results were comparable with those of other studies in the literature that used hamstring grafts, but without associated patellar complications. The superficial quad technique uses graft material that is a better anatomic match to the native MPFL. It provides anatomic patellar fixation without a bony procedure.